Implementation of Inquiry Learning to Enable Student Interaction on PAI Materials at SDI Musra - Ma’rifatul Mahbubah, Siti; Masnawati, Eli (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to examine the implementation of the inquiry-based learning model in enhancing student interaction in Islamic Religious Education (PAI) at SDI Musra. Inquiry-based learning is a student-centered approach where students are encouraged to ask questions, investigate, and find answers to their own questions. The research method used is descriptive qualitative with a case study approach. Data were collected through observation, interviews, and documentation, and analyzed using thematic analysis techniques. The results of the study show that the implementation of the inquiry-based learning model at SDI Musra is carried out through stages such as problem identification, question formulation, data collection, data analysis, and presentation of findings. The PAI teacher acts as a facilitator in this learning process. Inquiry-based learning successfully increases active student interaction, marked by active participation in discussions, question-and-answer sessions, and investigative activities. Students also show improvement in critical, analytical, and creative thinking skills. However, several challenges were faced, including time constraints, lack of supporting resources and teaching materials, and the varying levels of student ability. Teachers face challenges in managing a more dynamic and interactive class and facilitating each student to remain active and engaged. Proposed solutions include the development of more varied teaching materials, enhancement of teacher skills through training and workshops, and support from the school and parents. Overall, this study shows that the inquiry-based learning model has great potential in increasing active student interaction in PAI at SDI Musra. With proper planning and implementation, as well as support from various parties, inquiry-based learning can be an effective approach in achieving more holistic and in-depth religious education goals.